Analysis of flow characteristics in circular pipes - Dias, Eder; Soki, Francisco; Ramos, Neusa; Sebastião, Vemba; Ramos, Geraldo; Barros, António André Chivanga (Brazilian Journal of Science, 2025)
Determining the fluid flow regime is critical for optimizing oil production processes. To address this need, we evaluated a method for characterizing flow by calculating the Reynolds number. Experiments were conducted using a closed-loop piping system equipped with a flow meter and a visualization chamber. The flow rate was systematically increased, and all tests were performed in triplicate to ensure accuracy and reliability. The results showed that the experimental setup effectively distinguished laminar, transitional, and turbulent flows in both single-phase and multiphase systems, with transitions visually confirmed by observing streamlines. This study presents a validated and practical approach for accurately determining flow regimes, offering direct benefits for the design and operation of industrial flow systems.